The forty-yard dash for the high school athlete - Gough, M. (Strength and Conditioning Journal, 2006)
The 40-yard dash can be a useful tool for the high school coach with respect to assessment, talent analysis, and promotion of those athletes with high levels of speed and acceleration. The 40-yard dash can be enhanced through technique refinement and specific training.